The role of triiodothyronine hormone and mechanically-stressed endothelial cell paracrine signalling synergism in gene reprogramming during hBMSC-stimulated osteogenic phenotype in vitro - da Silva, Rodrigo A. [UNESP]; de Camargo Andrade, Amanda Fantini [UNESP]; da Silva Feltran, Geórgia [UNESP]; Fernandes, Célio Júnior da C. [UNESP]; de Assis, Rahyza Inacio F.; Ferreira, Marcel Rodrigues [UNESP]; Andia, Denise C.; Zambuzzi, Willian F. [UNESP] (Elsevier, 2018)
We therefore investigated whether there is synergism between triiodothyronine (T3) hormone and trophic molecules released from mechanically-stressed endothelial cells (EC-enriched medium) in osteogenic phenotype by mapping classical repertory of genes. Although there are studies reporting the efficiency of T3 hormone on bone cells, it is scarce considering their effect in conjunction with other physiologically active molecules, such as those released by the active endothelial cells. To address this issue, human bone marrow-derived mesenchymal stem cells (hBMSCs) were treated with EC-enriched medium subjected to shear-stress up to 72 h in vitro, in conjunction or not with T3 hormone. Although our results found an important synergism considering these parameters on modulating key bone-related gene markers, such as on the alkaline phosphatase (ALP) behavior (at both mRNA and protein content), contributing for osteoblast differentiation, important genes such as OSTERIX and RUNX2 were significantly down-expressed, while a over-expression of RANKL was found when the conjunction effect of T3 and endothelial paracrine signaling was considered. In addition, T3 hormone over expressed both OCT4 and NANOG genes in a DNA epigenetic-independent manner. However, we observed a dynamic reprogramming of DNMT1, DNMT3A, DNMT3B and TET1, important DNA-related epigenetic markers. Specifically, T3 hormone alone up-modulated TET2 transcripts profile. Complimentarily, expression of microRNA (miRs) processing-related genes also was modulated, as well as miR-10b, miR-22, miR-21, miR-143 and miR-145 transcriptional related profiles. Altogether, our results suggested a positive effect of mechanically-stressed endothelial cells-induced paracrine signaling on T3 hormone-obtaining osteogenic phenotype, contributing to understanding the paradoxal effect of T3 hormone on the bone physiology.
Keywords: Bone; Epigenetic; Mesenchymal stem cells; Osteoblast; Osteogenic phenotype; Thyroid; Triiodothyronine